PROMOSI JAJANAN SEHAT PADA SDN SAMATA - Fatmawati Malappiang; Yusma Indah Jayadi; Ummul Radia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2021)
Primary school age children are children aged 6 to 12 years. These children have a variety of activities so they often forget to eat breakfast and lunch so that instead they consume food that comes from school. Problems with unhealthy snacks for students must be dealt with to avoid various diseases. The Food and Drug Supervisory Agency (BPOM) conducted a survey involving schools in Indonesia and proved that 35% of school children 'snacks were unhealthy and did not meet the requirements. To reduce the consequences arising from unhealthy snacks, it is necessary to do socialization in schools, especially elementary school children. The purpose of the study was to provide education related to momentary snacks, how to choose healthy snacks and the impact of unhealthy snacks on SDN Samata students. The target of this activity is grade 5 students, with 25 participants. The method of socialization used is through the games method. Based on the results of the activities carried out that SDN Samata students have been able to distinguish between healthy foods and unhealthy foods. This is evidenced that the knowledge of participants about healthy snacks before the training is held there are students with good knowledge categories as much as 48% and 32% less categories. After the socialization, participants' knowledge increased to 68% in the good category, 24% in the sufficient category. Whereas knowledge of healthy snacks in the category of less decreased to 24%.